Then and Now: An Eight-Year Look at the U.S. Land·Grant University Agricultural Communications Profession, 1987-1995 - Robert E. Thomas (Journal of Applied Communications, 1996)
The purpose of this study was to examine selected trends and conditions pertaining to agricultural communications units in the U.S. land-grant institutions and to compare data obtained from a similar study conducted in the summer of 1987.